2022
DOI: 10.1021/acs.nanolett.2c03458
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Highly-Confined CsPbBr3 Nanorods with Enhanced Stability: Synthesis and Spectroscopy

Abstract: One-dimensional (1D) colloidal lead halide perovskites (LHPs) have potential as quantum emitters. Their study, however, has been hampered by their previous instability, leaving a gap in our understanding of structure–property relationships in colloidal LHPs with anisotropic shapes. Here, we synthesize stable, highly-confined 1D CsPbBr3 nanorods (NRs) and demonstrate their structural details and photoluminescence (PL) properties at both the ensemble and single particle levels. Using amino-terminated copolymers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…As aforementioned, the methods successfully applied in 1D CsPbBr 3 NC synthesis can be divided into six categories based on the common features of the method. 34–54 These methods are also categorized into two: direct synthesis methods and post-synthetic methods (Scheme 1). HIM, RTRM, and US are direct synthesis methods, while ICT, CC, and SA are post-synthetic methods.…”
Section: An Overview Of the Strategies For 1d Cspbx3 Nc Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…As aforementioned, the methods successfully applied in 1D CsPbBr 3 NC synthesis can be divided into six categories based on the common features of the method. 34–54 These methods are also categorized into two: direct synthesis methods and post-synthetic methods (Scheme 1). HIM, RTRM, and US are direct synthesis methods, while ICT, CC, and SA are post-synthetic methods.…”
Section: An Overview Of the Strategies For 1d Cspbx3 Nc Synthesismentioning
confidence: 99%
“…In addition to the mostly used OA/OAm ligand pair in HIM, some CsPbX 3 NWs or NRs were successfully synthesized using new ligand pairs. 35,54 Manna et al found that the width of the CsPbBr 3 NWs can be tuned using a mixture of alkyl amines and a short alkyl carboxylic acid. 35 Using a ternary ligand system of oleylamine/octylamine/hexanoic acid (Scheme 4), they synthesized CsPbBr 3 NWs and were able to tune the width of the NWs from 10 AE 1 (beyond the quantum confinement regime) to 3.4 AE 0.5 nm (within quantum confinement regime) by increasing the concentration of the short chain acid (Fig.…”
Section: An Overview Of the Strategies For 1d Cspbx 3 Nc Synthesismentioning
confidence: 99%
See 3 more Smart Citations